THE DEVELOPMENT OF VALUE SYSTEMS IN MALAYSIA: IN SEARCH OF EFFECTIVE INITIATIVES (Journal of Governance and Development (JGD), 2022)
In an effort to ensure that people in Malaysia have a strong character and at the same time have the ability to make mature decisions, they need to be guided by the right moral and ethical principles. In this regard, the development of society's value system requires a strong framework or foundation. However, what are the efforts and policies that develop and support the right value system? This study is under the 'interpretivism' paradigm and is qualitative in nature. The focus of this study is given to the concept of moral values. This study produces a list of important initiatives that are very crucial in the context of society's value system in Malaysia. The results of the research show that: the intervention of value education must be complete and have a comprehensive module or measure; special emphasis and continuous application of values; recognition and promotion of good values by providing special awards and mass promotions and involving all mediums; implementation in the form of a team and must be comprehensive rather than ad-hoc and one-off; an active discussion that involves various levels and continuous; formalize value education and provide a complete module as a guide; the creation of social imaginations and shared values; the study needs to be done continuously; guideline on the use of media and ensure development in a local context and adopting local culture. It will contribute to the existing work by providing considerable insights into value system initiatives in Malaysia.